RESPONS PERTUMBUHAN DAN PRODUKSI BIBIT G2 KENTANG (Solanum tuberosum L.) AKIBAT PERBEDAAN BOBOT UMBI BIBIT (G1) DAN KONSENTRASI PUPUK ORGANIK CAIR DI RUMAH KASA - Maria Masela S. Sitanggang; T. Irmansyah; Jasmani Ginting; Agustina br. br. Marpaung (Universitas Sumatera Utara, 2014)
The research was conducted at Screen house Experiment Berastagi at ± 1340 m asl from April untilJuly 2013 using split plot design with main plot, i.e. organic liquid fertilizer concentration (0, 2, 4,and 6 mL/L) and sub plot is tuber weight difference (≤ 3, 3-6, 6-9 and 9-12 g). Parameter observedwere plant height, duration of green leaves, tuber weight per plant, weight tuber per plot, and tubergrade percentage.The result showed organic liquid fertilizer treatment significantly defend thechlorophyll leaves (duration of green leaves). Tuber weight difference treatment significantlyincrease plant height, main stem number, tuber number per plant, weight tuber per plot and tubergrade percentage on 10,1 – 20 g. The interaction of two factor significantly increase tuber gradepercentage on ≤ 5 g. The best result was showed by organic liquid fertilizer concentration 6 mL/Land tuber weight 9-12 g.________________________________________________________________________________Keywords : weight tuber, organic liquid fertilizer, potatoes tuber